NATURAL PRODUCTS IN ORGANIC SYNTHESIS - ROBERT H. BURNELL (SEAMEO BIOTROP, 1996)
A resume of four lectures presented by the author during a one month visit to BIOTROP in 1995. The seminars were held at the University of Indonesia at Depok, the Technical Institute in Bandung, the Bogor Agricultural Institute and at BIOTROP, Bogor. The talks were grouped under the general title